Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia in a young man with hypoxia: a case report and review of the literature - Sami, Ramin; Mahzoni, Parvin; Rezaei, Marzieh (Acta Biomedica Atenei Parmensis, 2019)
Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) is a rare lung disease, which usually affects older women. This disease is often asymptomatic. For patients who are symptomatic, symptoms usually include cough and dyspnea. In this paper, we reported a 38-year-old man who suffered from chest pain for 3 months. CT scan findings revealed scattered nodules that were less than 1 cm. Spirometry was normal and the arterial oxygen saturation at room air was 85%. Open lung biopsy revealed DIPNECH. Patients with DIPNECH are mainly elderly women with symptoms including cough and dyspnea. However, we reported a young man with chest pain and hypoxia without dyspnea. DIPNECH can occur in male and female individuals at any age. (www.actabiomedica.it)